Photodetection Tuning with High Absorptivity Using Stacked 2D Heterostructure Films - Umar Farooq; Kossi A. A. Min-Dianey; Pandey Rajagopalan; Muhammad Malik; Damgou Mani Kongnine; Jeong Ryeol Choi; Phuong V. Pham (Nanomaterials, 2022)
Graphene-based photodetection (PD) devices have been broadly studied for their broadband absorption, high carrier mobility, and mechanical flexibility. Owing to graphene’s low optical absorption, the research on graphene-based PD devices so far has relied on hybrid heterostructure devices to enhance photo-absorption. Designing a new generation of PD devices supported by silicon (Si) film is considered as an innovative technique for PD devices; Si film-based devices are typically utilized in optical communication and image sensing owing to the remarkable features of Si, e.g., high absorption, high carrier mobility, outstanding CMOS integration. Here, we integrate (i) Si film via a splitting/printing transfer with (ii) graphite film grown by a pyrolysis method. Consequently, p-type Si film/graphite film/n-type Si-stacked PD devices exhibited a broadband detection of 0.4–4 μm (in computation) and obtained good experimental results such as the responsivity of 100 mA/W, specific detectivity of 3.44 × 106 Jones, noise-equivalent power of 14.53 × 10−10 W/(Hz)1/2, external quantum efficiency of 0.2, and rise/fall time of 38 μs/1 μs under 532 nm laser illumination. Additionally, our computational results also confirmed an enhanced light absorption of the above stacked 2D heterostructure film-based PD device compatible with the experimental results.